(untitled) (International journal of medical sciences, 2026)
Cyclophosphamide is an alkylating agent widely used in oncology, autoimmune diseases, and experimental immunosuppression models. Despite its therapeutic efficacy, cyclophosphamide induces profound immunotoxic and morpho-functional alterations in lymphoid organs, particularly the spleen. This literature review critically analyzes experimental data from the last decade, with special emphasis on splenic injury induced by cyclophosphamide in Chinchilla rabbits and other animal models. Experimentally, cyclophosphamide undergoes hepatic bioactivation, leading to oxidative stress, mitochondrial dysfunction, and activation of intrinsic apoptotic pathways. These molecular processes result in selective lymphocyte depletion, alterations in cytokine profiles, and disruption of splenic microarchitecture. From an immunological perspective, cyclophosphamide suppresses T- and B-cell proliferation, reduces the CD4⁺/CD8⁺ ratio, weakens the humoral immune response, and alters macrophage and dendritic cell function. Morphologically and functionally, white pulp atrophy, regression of germinal centers, reduction of the marginal zone, sinusoidal dilation, vascular congestion, and increased apoptotic index are observed. Oxidative stress and mitochondria-mediated apoptosis represent key mechanisms linking cellular injury to organ-level dysfunction. In rabbit models, including the Chinchilla breed, dose- and duration-dependent changes are generally similar to those observed in rodents; however, species-specific differences exist in lymphoid organization and regenerative capacity. This review integrates pharmacological, immunological, and histopathological findings, identifies methodological limitations, and outlines directions for future research.